2016
DOI: 10.1175/jamc-d-16-0121.1
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of WRF Downscaled Precipitation in Puerto Rico to Cumulus Parameterization and Interior Grid Nudging

Abstract: The sensitivity of the precipitation over Puerto Rico that is simulated by the Weather Research and Forecasting (WRF) Model is evaluated using multiple combinations of cumulus parameterization (CP) schemes and interior grid nudging. The NCEP–DOE AMIP-II reanalysis (R-2) is downscaled to 2-km horizontal grid spacing both with convective-permitting simulations (CP active only in the middle and outer domains) and with CP schemes active in all domains. The results generally show lower simulated precipitation amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
4
20
1
Order By: Relevance
“…Some important WRF model options include applying analysis nudging within the outer two domains and using a convective parameterization scheme for the innermost domain to reduce rainfall bias, as discussed in detail within Wootten et al . (2016). The following physics options were selected for the WRF simulations: Radiation—RRTMG (Iacono et al ., 2008) Microphysics—WSM6 (Hong and Lim, 2006) Planetary Boundary Layer—YSU (Hong et al ., 2006) Land Surface—Noah (Chen and Dudhia, 2001) Convection—Modified Kain Fritsch (Herwehe et al ., 2014) …”
Section: Model Experiments and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Some important WRF model options include applying analysis nudging within the outer two domains and using a convective parameterization scheme for the innermost domain to reduce rainfall bias, as discussed in detail within Wootten et al . (2016). The following physics options were selected for the WRF simulations: Radiation—RRTMG (Iacono et al ., 2008) Microphysics—WSM6 (Hong and Lim, 2006) Planetary Boundary Layer—YSU (Hong et al ., 2006) Land Surface—Noah (Chen and Dudhia, 2001) Convection—Modified Kain Fritsch (Herwehe et al ., 2014) …”
Section: Model Experiments and Evaluationmentioning
confidence: 99%
“…In particular, the CNRM 20th-century simulations improve the fidelity of the annual temperature cycle compared to other CMIP5 models (see figure 5 of Ryu and Hayhoe, 2014) and simulate the seasonal precipitation cycle that realistically reflects both a mid-summer drought and two precipitation peaks within the Caribbean (see table 3 of Hayhoe, 2013). et al, 2014) with significant rainfall reduction, −23%, for RCP8.5 by mid-century with a mean warming of 1.3 C. Finally, the best performing WRF configuration identified in Wootten et al (2016) was used in this study. Some important WRF model options include applying analysis nudging within the outer two domains and using a convective parameterization scheme for the innermost domain to reduce rainfall bias, as discussed in detail within Wootten et al (2016).…”
Section: Weather Research and Forecasting Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only one specific model configuration of a NWP was used in producing Vaisala's global wind maps. NWP studies for the Caribbean region have focused on a NWP's ability and sensitivity in predicting short-term heavy rainfall events in Puerto Rico, Barbados and Guyana [19][20][21] and hurricane evolution and associated storm surge [22][23][24]. Therefore, this study intends to optimize a NWP model output to produce more accurate model winds for one of the Caribbean small island states.…”
Section: Introductionmentioning
confidence: 99%
“…The WRF Double-Moment 6-class microphysics scheme [28] and the Grell 3D Ensemble Scheme Atmosphere 2020, 11, 91 9 of 30 cumulus parameterization scheme [29] are employed for both domains. Previous studies [30][31][32] have demonstrated that the activation of the cumulus parameterization scheme in the inner domain with high resolution improves the precipitation simulations. Since this study focuses on PM10 concentrations near the ground, the performance of the model for simulating near-surface wind fields is important.…”
Section: Wrf-chem Domain Configurationsmentioning
confidence: 99%